Impact of Humic Acids and Chitosan on the Ionic Composition of the Soil Solution and the Nutritional Content of Cabbage (Brassica oleracea L.) Under Greenhouse - Canales-Almendares, Jorge Enrique; Benavides-Mendoza, Adalberto; Ortega-Ortiz, Hortensia; Juárez-Maldonado, Antonio; Francisco-Francisco, Nazario (REVISTA TERRA LATINOAMERICANA, 2024)
Soil solution (SS) constitutes the volume from which plant roots extract dissolved nutrients. Despite its importance, the impact of its composition due to the application of organic amendments has been relatively little studied. The objective of this research was to study the impact of humic acids (HA) and chitosan (Cs) on the concentration of minerals in the SS, as well as their ef fect on the yield of the cabbage crop (Brassica oleracea L.). Under greenhouse conditions with calcareous soil, two doses of HA were applied (200 and 500 kg ha-1), as well as 50 and 150 kg ha-1 of Cs in a targeted manner. From the SS, 22 samples were taken non-destructively from the root zone once a week. The results of mineral content in the soil solution and mineral content on the biomass did not present significant dierences, however, it was noted that the Cs50 treatment stimulated 41% higher plant biomass than the control (P ≤ 0.5, Tukey). It is concluded that Cs and HA do not significantly impact the ionic content of the SS or the mineral content of the biomass, although they do stimulate the yield.